IDENTIFICATION OF EROSION RATE USING UNIVERSAL SOIL LOSS EQUATION (USLE) METHOD IN KOTO TANGAH DISTRICT PADANG CITY IN 2024: Inggris - Raju Mahendrik; Sri Kandi Putri (Remote Sensing Technology Study Program, 2025)
This study aims to analyze the erosion rate in Koto Tangah District, which is an area with varied topography and high rainfall. The area of ​​this area reaches 232.25 square kilometers, this area faces an increased risk of erosion due to human activities such as land clearing for agriculture and settlements. This study aims to: (1) calculate the erosion rate using the USLE method, and (2) map the distribution of areas with the potential for erosion in 2024. The formulation of the problem is focused on identifying the magnitude of the erosion rate and the distribution pattern of areas prone to erosion in Koto Tangah District. The research method uses the Universal Soil Loss Equation (USLE) approach integrated with the Geographic Information System (GIS). The data used include: rainfall data from CHIRPS 2024, soil type data from the Digital Soil Map of the World (DSMW) 2007, slope data from DEM, and land use data from the interpretation of Landsat imagery on October 8, 2024 using the Maximum Likelihood Classification method. The results of the analysis are expected to provide important information for the government and the community in disaster mitigation efforts and natural resource management. The study shows variations in erosion rates from <15 tons/ha/year to >480 tons/ha/year, with steep mountainous areas (>45%) showing the highest erosion rates. The discussion reveals that the interaction of slope factors, soil type, and land cover are the main determinants of the magnitude of erosion. Through a better understanding of erosion conditions in Koto Tangah, it is hoped that proactive steps can be taken to reduce the negative impacts of soil erosion and increase environmental resilience.